Perceptions of the Intervention Utility and Effectiveness in Supporting and Reintegrating Youths Born of Genocidal Rape in Rwanda - Nyirandamutsa F; Niyonsenga J; Gaju KL; Izabayo J; Kambibi E; Munderere S; Sebuhoro C; Muhayisa A; Sezibera V (Dove Medical Press, 2023)
Fortunée Nyirandamutsa,1 Japhet Niyonsenga,1,2 Kethina Lisette Gaju,3 Josias Izabayo,4 Emilienne Kambibi,5 Samuel Munderere,5 Célestin Sebuhoro,1 Assumpta Muhayisa,1 Vincent Sezibera1,4 1Department of Clinical Psychology, University of Rwanda, Kigali, Rwanda; 2Department of Humanities and Social Sciences, University of Parma, Parma, Italy; 3Global Mental Health MSc Program, King's College London and London School of Hygiene and Tropical Medicine, London, UK; 4Centre for Mental Health, University of Rwanda, Kigali, Rwanda; 5Department of Mental Health, Survivors Fund Rwanda, Kigali, RwandaCorrespondence: Fortunée Nyirandamutsa; Japhet Niyonsenga, Tel +250784010477, Email nyirandamutsaf@gmail.com; niyonsengajaphet74@gmail.comBackground: Birth through genocidal rape has a detrimental impact on the health of the offspring; however, there is scarce literature that focuses on efforts to support and reintegrate people born of this crime due to the lack of needs assessments that can inform policies and interventions.Objective: This study sought to explore perceptions of the intervention utility and effectiveness in supporting and reintegrating offspring born of the 1994 genocidal rape against the Tutsi in Rwanda.Methods: A purposive sample of 16 dyads of non-partnered mothers raped in the 1994 genocide against the Tutsi and their offspring participated in semi-structured qualitative interviews. The transcribed interview verbatims were uploaded to NVivo 12 and analyzed inductively using thematic analysis.Results: The analysis resulted in several subthemes that were grouped into four main themes based on research questions. These themes included the reconstruction of a positive image (ie, hardworking, contribution to the community, supporting vulnerable people, etc.), the benefits of collaborating with peers in a similar situation (ie, a sense of belonging, self-acceptance, relieving distress and emotional pain, etc.), the support obtained from Survivors Fund Rwanda (ie, psychosocial support, financial support for school fees, support to get a job), and the intervention and strategies needed (ie, continuous psychosocial support, catch-up learning programs, accompaniment support, advocacy to get a job, supporting the parents, etc.).Conclusion: Our results highlight how the youth born of genocidal rape are reconstructing a positive image and self-advocacy, their perception of obtained support, and the recommended intervention. These findings will help in initiating or strengthening interventions targeting this population, especially strategies to support and reintegrate them.Plain language summary: The current study was conducted to explore the perceptions of intervention utility and effectiveness in supporting and reintegrating offspring born of the 1994 genocidal rape against the Tutsi in Rwanda, which can inform policies and interventions. To achieve this, a purposive sample of 16 dyads of non-partnered mothers raped in the 1994 genocide against the Tutsi and their offspring were selected to participate in semi-structured qualitative interviews. Our analysis resulted in several subthemes that were grouped into four main themes based on research questions. These themes that emerged included the reconstruction of a positive image and self-advocacy, the benefits of collaborating with peers in a similar situation, the support obtained, and the intervention and strategies needed. These findings will help in initiating or strengthening interventions targeting people born of genocidal rape, especially strategies to support and reintegrate them.Keywords: genocidal rape, born of genocidal rape, needs assessment, intervention utilities, Rwanda, adolescent